ANALISIS KESALAHAN NAHWU DALAM MODUL AJAR BAHASA ARAB MI KELAS V DAN IMPLIKASINYA TERHADAP PEMBELAJARAN - Abdullah Ubaid; Diqi Agam Lubis; Gufron Gufron; Rohmatullah Salis (UIN Maulana Malik Ibrahim Malang, 2026)
This study is grounded in the importance of teaching modules as linguistic models in Arabic language learning at the Madrasah Ibtidaiyah level. The aim of this study to describe, classify, and analyze nahwu errors in the Grade V Arabic teaching module and to explain their implications for learning. This study employed a descriptive qualitative approach using the error analysis method. Data were collected through documentation of the Grade V Arabic teaching module and analyzed in stages of identification, classification, verification, and interpretation according to the rules of nahwu. The findings revealed ten naḥwu errors classified into six categories: idafah, jar majrur, na’t man’ut, mubtada’ khabar, fi’il mudari’, and ‘adad wa ma’dud. The most dominant errors were found in the idafah structure, followed by jar majrur and na’t man’ut. These findings indicate that the teaching module still contains inaccuracies in basic syntactic structures that should serve as the foundation of beginner-level Arabic learning. Pedagogically, these errors may lead to grammatical misconceptions, affect students’ understanding of Arabic sentence structure, and undermine the teaching module’s role as an accurate language model. This study emphasizes that linguistic evaluation of Arabic teaching modules is essential to ensure the grammatical accuracy of instructional materials. These findings contribute to the development of error analysis studies and to the improvement of the quality of Arabic teaching materials in Madrasah Ibtidaiyah.